PENINGKATAN KETERAMPILAN MENULIS CERPEN MENGGUNAKAN TEKNIK TERBIMBING DENGAN MEDIA CERPEN SISWA KELAS IX A SMP-IT AR RAHMAH PACITAN - Risda Puspita (sarasvati, 2020)
The purposes of this article is to explain the process and the improvement ability to write a short story using guided exercises at IX A SMP IT Ar Rahmah Pacitan student. This type of research finished by using descriptive method trough four stages in each cycle ie planning, action, observation and reflection. The research data in the form of short stories written tests, interviews, observations and field notes sheet student. Based on the results of the study concluded that the precycle average is 46,11% of the students qualified nearly enough, in cycle 1 is sufficiently increased to 65,29% in cycle 2 and the average value of student learning to write short stories increased to 89,61% with exelent qualifications.